Ringgit Malaysia predictability: do currencies and prediction horizon matters? - Tamat Sarmidi, (Penerbit Universiti Kebangsaan Malaysia, 2010)
The main objective of this study is to investigate the predictability of Malaysian ringgit against currencies that are regarded as fundamentally unstable. The study is motivated by a hypothesis that postulates the performance of exchange rate predictability is better-off for currencies with weak macroeconomic fundamentals or monetary instability. We employ bootstrap technique as proposed by Mark (1995) and later improved by Kilian (1999) to alleviate statistical inference intricacies inherit in the long horizon forecasting to three different monetary models (flexible, sticky and relative price) for ringgit against selected developing economies’ currencies. The empirical result shows the superiority of sticky price model for all prediction horizons along with the evidence of exchange rate predictability for ringgit against high inflation economies.